From India to China: Evolution of the Connotations of Extracanonical Buddhist Literature - Zhongyue Guan; Siyao Wang (Religions)
This paper introduces the concept of “Extracanonical Buddhist Literature” and explores its origins and development in the two major Buddhist cultural spheres of India and China. It investigates the roles such texts played in religious practice, doctrinal interpretation, and cross-cultural transmission. In India, extracanonical texts frequently remained outside the official canon due to factors such as sectarian divisions and geographic constraints, reflecting ongoing debates and dialogues with non-Buddhist thought. In China, the formation of these texts was influenced by indigenous cultural integration, political pressures, and translation practices, highlighting a distinct trajectory of Buddhist localization. By analyzing the complementary relationship between these extracanonical works and canonical scriptures, this study demonstrates that these texts not only supplement the canonical system but also offer critical insights into the diversity of Buddhist thought and cultural exchange. Ultimately, they hold significant academic and cultural value, shedding light on how Buddhist ideas were disseminated and adapted across diverse regional contexts.